2002
DOI: 10.1080/07481180290106571
|View full text |Cite
|
Sign up to set email alerts
|

Rates and Risks of Complicated Grief Among Psychiatric Clinic Patients in Karachi, Pakistan

Abstract: The aim of this study was to determine rates and risks of Complicated Grief (CG) among psychiatric clinic patients in Karachi, Pakistan. The Inventory of Traumatic Grief, an early version of Inventory of Complicated Grief--Revised, was administered to 151 recently bereaved patients, with validated criteria applied to determine CG "caseness." Thirty-four percent of the sample met criteria for CG. Although violent deaths did not pose a heightened CG risk, gender and kinship to the deceased did significantly incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
2
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 11 publications
6
43
2
2
Order By: Relevance
“…A large number of studies that examined differences in grief reactions within a relatively short period after the loss reported that time since the loss did not significantly impact the severity of prolonged grief symptoms or PGD diagnosis (Holland et al, 2006;Prigerson et al, 2002). Other researchers have found that grief reactions and coping may even worsen over time (Rando, 1983; Servaty-Seib & Pistole, 2 006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies that examined differences in grief reactions within a relatively short period after the loss reported that time since the loss did not significantly impact the severity of prolonged grief symptoms or PGD diagnosis (Holland et al, 2006;Prigerson et al, 2002). Other researchers have found that grief reactions and coping may even worsen over time (Rando, 1983; Servaty-Seib & Pistole, 2 006).…”
Section: Discussionmentioning
confidence: 99%
“…However, most studies have sampled bereaved persons using no substantial variability in the time since the loss (e.g., Holland, Currier, & Neimeyer, 2006;Prigerson et al, 2002). Therefore, the current study aimed to include a sample of mourners who varied considerably in time since the loss.…”
mentioning
confidence: 99%
“…These findings are corroborated by Burke and Neimeyer (2012) who identified being a mother of the deceased as a risk factor for developing CG. Also, Prigerson et al (2002) found that parents were 11 times more likely to meet criteria for CG than other kinship types. Given the connection between severe grief responses of close kin in relation to violent death loss, the current case study will highlight the experience of a mother bereaved by homicide.…”
Section: The Role Of Kinshipmentioning
confidence: 97%
“…El duelo complicado resulta mucho más probable después de muertes repentinas o violentas, como los fusilamientos del franquismo. Y el duelo complicado conlleva con frecuencia consecuencias físicas adversas; acrecienta la probabilidad de sufrir enfermedades cardíacas, cáncer, hipertensión y problemas psiquiátricos (Jacobs y Prigerson 2000;Prigerson 1997Prigerson , 2002.…”
Section: Revista De Dialectología Y Tradicionesunclassified